Crazy : a father's search through America's mental health madness - Earley, Pete. (New York : Berkley, 2007)
The author shares his frustrating experiences trying to get help for his son, Mike, who began having psychotic episodes when he was in his early twenties, and discusses what he learned about the state of the mental health system in the U.S. through his investigations inside the Miami-Dade County jail.
Includes bibliographical references
Keywords: Mental illness; Mental illness -- Case studies; Mentally ill -- Biography; Mentally ill -- Family relationships; Parent and child; Biography